Control Optimization through Simulations of Large Scale Solar Plants for Industrial Heat Applications. (May 2015) - Hassine, Ilyes Ben; Sehgelmeble., Mariela Cotrado; Söll, Robert; Pietruschka, Dirk
Abstract: The European FP7 Project InSun; which started in April 2012; aims to demonstrate the reliability and efficiency of three different collector technologies suitable for heat production employed in diverse industrial processes in different climatic regions. These collectors are installed and will be monitored in detail over a period of almost two years. One of the plants is installed at Fleischwaren Berger GmbH located in Sieghartskirchen, Austria, a company which produces meat and sausage products. The second solar plant is installed at the company Laterizi Gambettola SRL (SOLTIGUA) located in Gambettola, Italy, which produces highly insulating hollow brick blocks for external walls of buildings. The control optimization and commissioning of the two solar plants has been carried out as a part of the InSun project. Considering measurements and results of simulations developed with dynamic models, potential improvements of the low-level control algorithms are presented for the two solar plants.